The sensitivity of photosynthesis to magnesium deficiency differs between rice (Oryza sativa L.) and cucumber (Cucumis sativus L.) - Meng, Xusheng; Bai, Song; Wang, Shiyu; Pan, Yonghui; Chen, Kehao; Xie, Kailiu; Wang, Min; Guo, Shiwei (Frontiers in Plant Science, 2023)
Magnesium is an essential macronutrient for plant photosynthesis. Dicots appeared more sensitive than monocots in response to Mg-deficiency. This study aims at investigating the cause of differing sensitiveness between different plant species on photosynthesis under Mg deficiency. Rice (Oryza sativa L.) and cucumber (Cucumis sativus L.) were grown in hydroponic culture to investigate their response to Mg-deficiency stress. Physiological characteristics were analysed after a few weeks. Both Mg-deficient rice and cucumber plants exhibited lower biomass, leaf area, Mg concentration and chlorophyll content (Chl) compared with Mg-sufficient. However, more marked decline in Chl and carotenoids content (Car) occurred in cucumber. A lower CO2 concentration in chloroplasts (Cc) accompanied with the decreased the maximum rate of electron transport (Jmax) and the maximum rate of ribulose 1,5-bisphosphate carboxylation (Vcmax) restricted CO2 utilization in Mg-deficient plants. There were increases in photorespiration rate (Pr) of rice and cucumber under Mg-deficiency. Additionally, Car and non-photochemical quenching (NPQ) of cucumber were reduced in lower Mg supply, and a positive correlation also was found between Car and NPQ. Under Mg-deficiency suppressed photosynthesis was attributed to comprehensive restrictions of mesophyll conductance (gm), Jmax and Vcmax; cucumber was more sensitive than rice to Mg-deficiency attributed to lower NPQ instead of lower photorespiration rate.